Implementation of Amoi Marriage Custom in Marriage Procedures in Rumahkay Village - Gosye A. Jehubyanan; F. Sialana; Ridwan Hatala (IJRAEL: International Journal of Religion Education and Law, 2022)
The amoi tradition is a tradition that has been carried out in the life of the rumahkay community passed down from generation to generation which refers to a culture of marriage customs and is more focused on the process of accepting the bride into the house (the groom's old house). The heritage of the ancestors that already exists needs to be built and preserved as a form of cultural wealth, this heritage cannot be extinguished because it contains an element of education in shaping the character of the community in order to still carry out the Amoi marriage custom. This research aims to find out and give an explanation related to the tradition of implementing Amoi marriage customs as one of the marriages in Rumahkay village. by using 2 indicators 1. What is the procedure for handing over property in the custom of amoi marriage (maso mata rumah) in a custom marriage in rumahkay village, amalatu subdistrict, seram regency in the west. 2. What are the supporting and inhibiting factors in the custom of amoi marriage (maso mata rumah) in the community of rumahkay village, amalatu district, seram regency in the west. The method used in this research is qualitative, and data collection techniques, observation, and interviews as well as data analysis techniques. Based on the results of the research that the Amoi marriage procedure is carried out in the life of the Rumahkay village community because the Amoi tradition is a custom that until now is still inherited in the life of the masyaratkat, in this case a consultation is held where the village head, village officials, traditional elders and both grooms and women are in a meeting together to carry out the marriage process. In the Amoi marriage procedure there are two factors, namely supporting and inhibiting factors in carrying out the process where the supporting factor such as in the implementation of the said custom must have the consent of both the bride and groom in this case the parents allow the child to build a household with people who has been chosen to be a husband or wife. However, the inhibiting factor is an action that is not agreed by one party, for example the woman's party cancels the marriage process because the man's party does not have the property that has been determined in the customary meeting.